The improvement of Artificial Intelligence in Religious Education and Moral Achievement - Budi Santoso; Ainur Rofiq; Nur Hidayati; Moh Nur Fauzi; Siti Aimah (Education and Sociedad Journal, 2025)
This study aims to examine the impact of implementing AI in improving the quality of religious learning and students' moral achievement at madrasas. This research is driven by the challenge of increasing the effectiveness of in-depth religious learning, which requires a broad and contextual understanding, amidst the limited access to education. The research method used is a case study with a qualitative approach, involving observation and interviews with students and teachers, the results of which are then analyzed using the Miles and Huberman approach. The research findings show that the application of AI in religious learning can provide relevant and personalized materials, increase accessibility, and support flexible learning. In addition, positive reinforcement has been shown to increase students' self-confidence which contributes to increasing their participation and academic achievement. Emotional resilience supported by an empathetic approach from teachers has also been shown to increase students' mental resilience, help them cope with academic and social pressures, and play a role in achieving better morals. The contribution of this research is to provide insight into the importance of integrating AI, positive reinforcement, and emotional resilience in improving the quality of religious education and students' moral achievement, which can be used as a model for the development of religious education in the future.